2018
DOI: 10.1029/2018gl080145
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Electron Cyclotron Harmonic Waves as a Candidate to Cause Pulsating Auroras

Abstract: Pulsating auroras (PsAs) are thought to be generated by precipitating electrons scattered by lower‐band chorus (LBC) waves near the magnetic equator. One‐to‐one correlation between the LBC intensity and the PsA intensity has been reported. Electrostatic electron cyclotron harmonic (ECH) waves can also scatter electrons. However, direct correlation between ECH and PsA has not been reported yet. In this study, using a coordinated Exploration of energization and Radiation in Geospace (Arase) satellite and ground‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…The ultimate source of pulsating aurora is generally accepted to be magnetospheric electrons with energies of a few to tens of keV (Bryant et al, 1971;Sandahl et al, 1980). Recent studies have further shown that the precipitation is driven by wave-particles interactions (e.g., Fukizawa et al, 2018;Liang et al, 2010;Nishimura et al, 2010); however, the mechanism that determines the pulsation period and the shape of patches has not been determined. Previous studies of the optical emissions associated with pulsating aurora found that the emissions typically come from 110-km altitude (Davidson, 1990;Johnstone, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The ultimate source of pulsating aurora is generally accepted to be magnetospheric electrons with energies of a few to tens of keV (Bryant et al, 1971;Sandahl et al, 1980). Recent studies have further shown that the precipitation is driven by wave-particles interactions (e.g., Fukizawa et al, 2018;Liang et al, 2010;Nishimura et al, 2010); however, the mechanism that determines the pulsation period and the shape of patches has not been determined. Previous studies of the optical emissions associated with pulsating aurora found that the emissions typically come from 110-km altitude (Davidson, 1990;Johnstone, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…The resonance energy of LBC reaches 9 keV at the MLAT of −3° in this event. Although ECH and LBC waves were concurrently excited for this event, it can be considered that the difference between their cyclotron resonance energies differentiated their contributions to the pitch‐angle scattering of inner magnetospheric electrons (Fukizawa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent statistical observations and theoretical predictions support the importance, and even dominance, of the whistler chorus in scattering energetic electrons out of the plasma sheet for L shells ≤8 (Li et al, 2005;Santolik et al, 2009;Thorne et al, 2010). Other observed statistics support the dominant scattering effect of electron cyclotron harmonic (ECH) waves at L shells > 8 (Liang et al, 2010;Ni, Thorne, Liang, et al, 2011;Zhang et al, 2015) and an association between intense auroral forms and ECH waves at about L = 6 (Fuzikawa et al, 2018). Other observed statistics support the dominant scattering effect of electron cyclotron harmonic (ECH) waves at L shells > 8 (Liang et al, 2010;Ni, Thorne, Liang, et al, 2011;Zhang et al, 2015) and an association between intense auroral forms and ECH waves at about L = 6 (Fuzikawa et al, 2018).…”
Section: Introductionmentioning
confidence: 87%